STUDENTS' MATHEMATICAL REPRESENTATION ABILITY IN SOLVING MATHEMATICS QUESTIONS BASED ON HIGH ORDER THINKING SKILLS - Ambarani, Erli; Yunianta, Tri Nova Hasti (Universitas Papua, 2021)
The ability of representation is part of the five basic standards in learning mathematics. This ability needs to be possessed by students well. Analyzing and describing the representational abilities of junior high school students in solving mathematics based on Higher Order Thinking Skills is the aim of this study. This type of research is descriptive qualitative research. The subject of this study found 4 students taken from 26 students of class IX A SMP Negeri in Temanggung Regency who have high mathematical abilities. The data collection technique of this research used tests, interviews, and documentation. The validity of the data using data triangulation. The data analysis technique used is data reduction, data presentation, and conclusion drawing. The results of the analysis and research descriptions show that students' representational abilities in solving HOTS-based math problems are different. The verbal representation category of S2 and S3 subjects can use verbal representations well and has concluded that S1 has not yet completed the steps, and S4 has not been able to write down the steps on verbal representation. The ability of symbolic representation of subjects S1, S2, S3 still has errors in writing equations but does not affect the results, S4 already assumes equations and expressions correctly. The visual representation categories S1, S2 and S4 have not been able to draw geometric shapes completely, while S3 is wrong in writing symbols on the picture.